Pemanfaatan Ilmu Pengetahuan dan Teknologi dalam Pendidikan - Bakhrudin All Habsy; Amelia Putri Eka Yusiana; Naila Nadya; Ardiansyah Fahmi Satria (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The progress of a country can be supported by the quality of its human resources. The use of Science and Technology (IPTEK) continues to expand along with the development of the times, thus providing implications for the development of education. The progress of technology and science are two things that greatly influence the development of a country. The use of Science and Technology (IPTEK) in education has become the main focus in improving the quality of learning and teaching effectiveness. This study aims to increase readers' insight into the importance of improving the quality of human resources by improving education in Indonesia, one of which is through the development of an education curriculum based on science and technology. This study uses qualitative research with a literature study type. The results of this study include (1) The Foundation of Science and Technology (2) The Development and Sustainability of Science and Technology (3) The Impact and Influence of Science and Technology (4) Utilization of Technology (5) Utilization of Science and Technology (6) The Role of Technology in Education (7) The Importance of Science and Technology.